2021
DOI: 10.1038/s41420-021-00667-x
|View full text |Cite
|
Sign up to set email alerts
|

Gadd45g initiates embryonic stem cell differentiation and inhibits breast cell carcinogenesis

Abstract: Many self-renewal-promoting factors of embryonic stem cells (ESCs) have been implicated in carcinogenesis, while little known about the genes that direct ESCs exit from pluripotency and regulate tumor development. Here, we show that the transcripts of Gadd45 family genes, including Gadd45a, Gadd45b, and Gadd45g, are gradually increased upon mouse ESC differentiation. Upregulation of Gadd45 members decreases cell proliferation and induces endodermal and trophectodermal lineages. In contrast, knockdown of Gadd45… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(13 citation statements)
references
References 58 publications
0
13
0
Order By: Relevance
“…More importantly, these four genes are closely related to cell development and differentiation. It has been reported that the expression of GADD45B is increased upon embryonic stem cells differentiation ( Zhang et al, 2021 ). Meanwhile, GADD45B is considered as a myeloid differentiation primary response gene ( Abdollahi et al, 1991 ).…”
Section: Resultsmentioning
confidence: 99%
“…More importantly, these four genes are closely related to cell development and differentiation. It has been reported that the expression of GADD45B is increased upon embryonic stem cells differentiation ( Zhang et al, 2021 ). Meanwhile, GADD45B is considered as a myeloid differentiation primary response gene ( Abdollahi et al, 1991 ).…”
Section: Resultsmentioning
confidence: 99%
“…A decrease in the expression level of this protein is associated with a wide variety of oncological diseases of different histogenesis. With regard to BC, there is evidence that the GADD45g protein inhibits the growth of human BC cells in vivo and in vitro, acting as an antitumour agent (Zhang et al, 2021). Moreover, the antitumour effect of the GADD45g protein can be realised independently of other important molecular factors that counteract carcinogenesis (P53, pRB, etc.…”
Section: Advances Inmentioning
confidence: 99%
“…Te 45G (GADD45G), a member of the GADD45 family, participates in DNA damage response and cell growth arrest. Studies have confrmed that GADD45G is lowly expressed in esophageal squamous cell carcinoma, breast cancer, and acute myeloid leukemia [14][15][16]. It has also been reported that the upregulation of GADD45G expression induces the senescence of HCC cells [17].…”
Section: Introductionmentioning
confidence: 99%